Development of Comic-based Akidah Akhlak Teaching Materials on Praiseworthy Morals in Madrasah Ibtidaiyah - Permadi, Benny Angga; Hassan Sain, Zohaib; Thelma, Chanda Chansa; Alai, Ashimatul (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study aims to develop comic-based teaching materials for the Akidah Akhlak subject, specifically on Living in Harmony and Neighborly Relations for fifth-grade students at MIN 2 Mojokerto, in the form of a printed book as a learning media. The design of this research is a Research and Development (R&D). The model used is a procedural model adapted from Dick & Carey’s development model. The results of this research are as follows: (1) comic book-based learning materials developed by simply presenting arranged pictures and equipped with balloon texts can improve the quality of students learning. (2) the material presented in developing learning materials based on this comic is only for the aqidah akhlak subjects, Neighborly Life, and community material of fifth grade of MIN 2 Mojokerto. (3) the eligibility of comic-based materials is done by three test experts, namely (a) the percentage of material experts acquire 85%, (b) the design learning materials expert gets a percentage of 86,6%, and (c) the practitioner or teacher gets 88,3%. Based on the survey, the three test experts believe comic-based materials are worth using as learning materials. (d) The interest in comic-based materials was obtained from the survey assessment performed by students, with an acquisition value of 88.8%. (4) The effectiveness of materials-based comics was assessed using a field test. Based on the field test, it can be concluded that the product materials-based comics produced are effectively used in learning. The paired analysis results showed a significant influence between the pretest and posttest. Based on ? 0.05 and df 19, then retrieved the t table 2,093 field test data retrieved that calculation based on a test-t sample of - 15,567 < -2,188 or t count lies in the area on the rejection of H0. Thus, learning by using comics-based materials in the learning material Living Neighborly Attitudes and Community can be used as learning materials that encourage the students to learn independently and guided. This study shows that comic-based teaching materials can effectively engage students and improve their understanding of Akidah Akhlak, especially on topics like living in harmony and neighborly relations. Using comics, teachers can create more interactive and enjoyable learning experiences that help students grasp moral and social values. This research suggests that comic-based materials can be a valuable tool in the classroom. It encourages further exploration of using comics in other subjects to enhance student engagement and learning outcomes.